Przemiany na wspólnotowym rynku cukru w nowych warunkach gospodarczych - Lipińska, Izabela (Wydawnictwo Naukowe UAM, 2007)
1 July 2006 witnessed the reform of sugar market, one o f the sector-specific agricultural markets organisations functioning within the European Union. On the one hand that reform was prompted by the imminent accession to the EU of new members (Rumania and Bulgaria) and on the other, it was pursued in response to the pressures of the WTO, which demanded liberalisation of the Community sugar market, and in particular the lowering of official sugar price and the opening of that market to third countries. The new legal framework resulted in many modifications in the functioning of the sugar market in respect of the production quotas, guaranteed prices, sugar storage, or support for sugar beet growers. The latter, pursuant to the binding regulations, must re-new their sector contracts with sugar producers. Having in mind the situation in the world sugar market, the Community legislator provided for restructuring payments, which are now a new instrument with which to stimulate sugar production within the Community. The first sugar campaign under the new conditions is coming to an end but very few of the assumptions of the new reform have been attained. The new legal instruments that have been implemented do not always perform as expected. Consequently, the legal organisation of the sugar market after the reform is still in need of further modification.
TRANSFORMATIONS ON THE COMMUNITY SUGAR MARKET IN NEW ECONOMIC CONDITIONS